Esquema único de tratamento da hanseníase : influências das formas clínicas nos efeitos indesejáveis dos fármacos - Gonçalves, Heitor de Sá (2010)
Leprosy control is based on early treatment of the patient and interruption of transmission. On current days, a new challenge for this control presents itself: the applicability of one single treatment regimen for all clinical forms of the disease, denominated Uniform Multidrug Therapy (U-MDT), an effective and short regimen, capable of overcoming the following issues: mistakes in the classification of clinical forms, drugs side effects, treatment abandon and its costs. Many diseases, malaria being the main example, present differences in effectiveness and side effects of drugs, according to the different pathological agents and clinical forms. This is due, amongst other possibilities, to differences in the metabolism of these drugs. Leprosy, with different and spectral clinical forms (indeterminate, tuberculoid, borderline tuberculoid, borderline borderline, borderline lepromatous, lepromatous), also presents, in function of those forms, bacteriological, histopathological, immunological and genetic differences. Possible issues to be faced by the U-MDT would be differences in the therapeutical effectiveness and pharmacological side effects, according to the spectrum of the disease. On this thesis, we try to evaluate the incidence of side effects of the drugs dapsone, rifampicin and clofazimine, used in the treatment of leprosy. Forty patients of the tuberculoid form were selected, from which 20 (twenty) used the standard regimen with dapsone and rifampicin and 20 (twenty) used the regimen with dapsone, rifampicin and clofazimine, denominated U-MDT. We also selected twenty patients of the borderline lepromatous and lepromatous forms, who used the U-MDT regimen. All patients received six doses of treatment. In all treated patients were not evidenced side effects that could lead to the interruption of treatment. With the exception of hemolytic anemia, which occurred in high incidence in both groups of patients that used the U-MDT regimen, other side effects were present in low incidence, compatible with the scientific evidences, in all groups of patients. There was no difference in the findings of hemolytic anemia, or other side effects, according to the clinical forms of the tuberculoid patients (paucibacillary) and borderline lepromatous or lepromatous (multibacillary) patients who used the U-MDT regimen. Such data suggests the inexistence of influence of the clinical forms of the disease on pharmacological side effects. The verification of highest incidence of hemolytic anemia, attributed to dapsone, in the groups of patients treated with U-MDT in comparison to the group of patients treated with dapsone and rifampicin, seems to suggest some role of clofazimin in the genesis of such side effect.